Estimation of angiotensin peptides in biological samples by LC/MS method - Ali, Quaisar (2013)
The low abundance of angiotensin peptides in biological tissues such as the kidney cortex, adipose tissue, urine and plasma makes their detection and quantification a challenge. A few available methods used to quantify these peptides involve lengthy processes of sample preparation and are hardly quantitative. Here, we report a mass spectrometry approach for quantifying angiotensin peptides [Ang II, Ang-(1-7)] in the kidney cortex, epididymal white adipose tissue (eWAT), urine and plasma of male mice. Tissue homogenates, urine and plasma samples were solid-phase extracted with C18 Sep-Pak cartridges and eluted off proteinaceous compounds. These extracted peptide samples were separated on C18 column with a linear acetonitrile gradient and detected by Q-ToF mass analyzer in ESI+-MS ion mode based on their retention time, accurate mass measurement of peptides, the isotope pattern of doubly charged molecular ion, and quantitation of peak area (or ion count) when referencing to the angiotensin peptide standards. The lower limit of quantitation for each angiotensin peptide was 10 pgmg(−1) with the percent recovery at 100.6%. The intra-batch precision for Ang-(1-7) and Ang II were 24.0 and 12.7%, accuracy 84.0–123.0% and 100.2–116.0% respectively. Using this method, we determined the levels of Ang II and Ang-(1-7) in the kidney cortex, eWAT, urine and plasma. Quantification of angiotensin peptides could help target subtle therapeutics changes against pathophysiological conditions such as obesity, kidney disease and hypertension.